Pendampingan Penguatan Komite Pembelajaran 3 “Merancang dan Memandu Refleksi” Program Sekolah Penggerak di Kabupaten Soppeng - Rahma Ashari Hamzah Hamzah (Madani : Indonesian Journal of Civil Society, 2022)
The Mentoring Activities for Strengthening the Learning Committee 3 focuses on designing and guiding reflection activities, which are part of the mentoring activities carried out by expert trainers at the Motivating School Program in Soppeng Regency to provide a better understanding of the implementation of an independent curriculum in the learning process. Expert trainers are here as facilitators who facilitate the strengthening of the learning committee 3 where the participants are the learning committee (school supervisors, principals, and teacher representatives who have attended training on the implementation of Activating School learning at the national level), and those who attend this activity are assisted schools. Expert trainers for this Motivating School Program which consists of 4 schools, namely SMA Negeri 5 Soppeng. SMP Muhammadiyah Lajoa, SMP Negeri 1 Watansoppeng, and SMP Negeri 1 Marioriwawo. This activity was held in the form of a workshop, the agenda of activities starting from the opening; guided self-learning: learning from experience; guided self-learning feedback; preparation facilitates reflection; prepare a moderation plan for the reflection session; identification of challenges in building a culture of reflection; formulating alternative solutions to challenges in building a culture of reflection; reflection: designing and guiding reflection; sharing learning committee good practices; learning committee reflection; and the last one is closing. This activity has an impact on participants in understanding the essence of reflection, the benefits of doing reflection, preparation before facilitating a reflection session, various strategies/methods in reflection, preparation of a moderation plan for reflection sessions, and identification of challenges that may occur in building a culture of reflection. In addition, Participants also gain skills in formulating key reflection questions in a positive atmosphere (the purpose of their development) and can arrange a moderation plan for reflection sessions.